A national survey on the effective use of the CDRI and educational TV programme in Malaysian schools - Mokhtar, Fattawi; Sheikh Ahmad, Ismail; Abdullah, Wan Mohd Rani; Mohd. Asraf, Ratnawati (Malaysian Educational Technology Association, 2010)
The purpose of this study is to evaluate the effectiveness of the teaching and learning materials developed by the Educational Technology Division, Ministry of Education Malaysia. The materials were tested in a variety of teaching and learning modes involving different learners’ characteristics. In a nutshell, this study investigates the motivational level of the materials and related issues in developing and using them in the process of teaching and learning in schools. A total of 10 resource materials in the form of compact discs and educational television programmes (Rancangan TV Pendidikan) covering 10 topics in the teaching and learning of Science and Mathematics for year five (primary school) and form two (lower secondary school) were carefully studied. A total of 7,956 learners and 130 teachers involving 130 primary and secondary schools throughout the country and 12 related officers of the Educational Technology Division were chosen through a stratified random sampling method for this evaluative study. A survey, quasiexperimental and semi-structured interview methods were used to yield quantitative and qualitative data respectively. The independent variables for the quasi-experimental design involve two main factors; teaching and learning mode and learners’ abilities. The results of this study show that the post-test scores of the content of the resource materials for all topics and categories of materials tested, particularly in the mastery of the difficult, quite difficult, quite easy, and easy concepts show an increase when compared to the pre- test scores. The comparison involves the low, medium and high academic achievers for every tested resource material. However, the increased scores of the mastery of the materials were not the same.